The Way to Increase the Motor and Sport Competence Among Children: The Contextualized Sport Alphabetization Model - González-Víllora, Sixto; Sierra-Díaz, Manuel Jacob; Pastor-Vicedo, Juan Carlos; Contreras-Jordán, Onofre Ricardo (Frontiers in Physiology, 2019)
There is a concern to implement games that will be able to increase the students’ motor and sport competence during the sport contents in Physical Education. Some games encompassed in Models-Based Practice (MsBP) are more beneficial for physical and physiological development than others. The main purpose of this study is to compare the degree of physical and physiological performance in several futsal games that have been implemented through two MsBP: the Teaching Games for Understanding (TGfU) and the Contextualized Sport Alphabetization Model (CSAM). The second objective is to analyse the relationship between physical and physiological variables. A quasi-experimental and cross-sectional study with pre- and post-test evaluations had been carried out. The sample was composed of 112 Primary Education students from First to Sixth grade (9.35±1.76 years). Polar Team Pro® technology was implemented to compare and analyse the physical and physiological variables. Data was analyse comparing both models with a two-step cluster model. Afterwards, T-Student test was executed to compare the progression of both models. Besides, two-level multilevel model (MANOVA-ANOVA, followed by MANCOVA- ANCOVA) were also executed by means of applying a 4 versus 4 Small-Sided and Conditioned Game (SSCG). Finally, Pearson correlation between physical and physiological variables was calculated. Results showed that physical and physiological performance was higher in CSAM groups. In this regard, throughout the intervention of both models, results showed significant differences in physical and physiological variables at SSCGs implemented in the CSAM over the games implemented during the TGfU. Additionally, multilevel and MANCOVA post-test analyses shows significant differences in the physical and physiological performance during the post-test 4 vs. 4 SSCG at the CSAM students, in contrast to the TGfU students (p<0.001). These results demonstrate that both physical (e.g. distance covered) and physiological performance (e.g. Edwards’ TRIMP) are significantly higher during CSAM in contrast to TGfU. Moreover, relationship between physical and physiological variables help teachers to adapt sessions to the features of the context.